Analisis Dan Perancangan Dashboard dan Modul Admin Sistem Manajemen Konferensi - Pandu Damar Priambodo; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Currently, the application of technology is widely used in many fields. Without exception the field of organizing or management for scientific conferences. The application of technology in this field is needed to provide improvements in organizing a conference. Currently there are several conference management systems, including the Open Conference System (OCS), ConfTool, EasyChair, and OpenConf. In the existing system, the conference organizer registers the conference to one of these systems, and then the link or web link is shared by the organizer on the publication path that has been made regarding the conference (Call for Paper). The existing system already has functional requirements properly. However, there is a need for a system with a display that can package scientific conferences in a more attractive manner and give a positive impression and interest to the participants in general. Therefore it is necessary to have a system or dashboard that is able to regulate how scientific conferences are available and bring together between a scientific conference and participants who are interested in the scientific conference more easily, interestingly and effectively, so that later an effective service can be realized, efficient and quality service. System testing will be carried out using the usability testing method. From the test results and calculations obtained for each aspect of the assessment are as follows: the effectiveness aspect with a score of 95%, the efficiency aspect with a score of 91.6%, and the satisfaction aspect with a score of 65.5%. From all aspects, it is calculated on average with the final score of usability testing of 84.03% which is included in category A (excellent).